Description of Google Classroom-Assisted STEM Learning to Improve Students' Mathematical Creative Thinking Skills - Ari Widiastuti; Nila Ubaidah; Dyana Wijayanti; Maeliyastuti Mafatihatur R. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The learning strategy implemented in schools focuses on teacher centered learning caused the students' mathematical creative thinking skills are not optimally honed. Efforts to shift learning from teacher centered learning to student centered learning are the STEM approach aided google classroom so that students can develop mathematical creative thinking skills optimally. This study aims to determine the STEM approach aided google classroom to improve students' mathematical creative thinking skills in line and angle material. The research method used is descriptive qualitative. The research was conducted in class VII A SMP Negeri 1 Pucakwangi consisted of 28 students. The research subjects were determined using purposive sampling technique. The data analysis techniques were written tests, questionnaires and interviews. The results showed that the approach of STEM aided google classroom is a learning strategy that is able to transform teacher-centered learning into student-centered learning. Students can follow the learning well, interactive so that it runs effectively. The STEM approach is able to improve students' mathematical creative thinking abilities optimally. Mathematical creative thinking able are grouped high, medium and low based on the process and written test scores. The pre-test result showed 1 student (3.6%) was in high category, 7 students (25%) were medium, and 20 students (71.4%) were low. While the results post-test showed that 7 students (25%) were in high category, 19 students (67.9%) were medium, and 2 students (7.1%) were in the low. This shows that there is a significant increase from the low category to the medium and high categories.